Efficiency Analysis of Zakat Management Institutions in Banyumas Regency: Case Study of LAZISMU, LAZISNU and BAZNAS - Afief El Ashfahany; Muhammad Iqbal Nur Ishlahudin (Universitas Wahid Hasyim Semarang, 2023)
In the economic field, zakat has a role as an effort to prevent the accumulation of wealth in only one community, therefore must be managed properly.This study focuses on discussing the efficiency of a zakat management institution in Banyumas district. This study discusses two private zakat institutions (LAZISMU Banyumas, and LAZISNU Banyumas) and one Government Zakat institution (BAZNAS Banyumas). This research uses the Data Envelopment Analysis method. This study also uses quantitative methods and uses secondary data types derived from financial report data for 2018, 2019, and 2020 from LAZISMU Banyumas, LAZISNU Banyumas, and BAZNAS Banyumas. The variables used in this research are input and output variables. The input variables consist of assets and operational costs. The output variable consists of collected zakat funds and distributed zakat funds. The results of this study are that in 2018 LAZISMU and LAZISNU experienced inefficiency in the CRS approach, but in the VRS approach the three zakat institutions were efficient. In 2019 LAZISNU experienced inefficiency in the CRS approach, but in the VRS approach.Keywords: Effectiveness; Harmony; ToleranceAbstrakDalam bidang ekonomi, zakat berperan sebagai upaya mencegah penumpukan kekayaan hanya pada satu golongan, oleh karena itu harus dikelola dengan baik. Kajian ini fokus membahas efisiensi lembaga pengelola zakat di Kabupaten Banyumas. Kajian ini membahas tentang dua lembaga zakat swasta (LAZISMU Banyumas, dan LAZISNU Banyumas) dan satu lembaga zakat Pemerintah (BAZNAS Banyumas). Penelitian ini menggunakan metode Data Envelopment Analysis. Penelitian ini juga menggunakan metode kuantitatif dan menggunakan jenis data sekunder yang berasal dari data laporan keuangan tahun 2018, 2019, dan 2020 dari LAZISMU Banyumas, LAZISNU Banyumas, dan BAZNAS Banyumas. Variabel yang digunakan dalam penelitian ini adalah variabel input dan output. Variabel input terdiri dari aset dan biaya operasional. Variabel output terdiri dari dana zakat yang terkumpul dan dana zakat yang disalurkan. Hasil penelitian ini adalah pada tahun 2018 LAZISMU dan LAZISNU mengalami inefisiensi pada pendekatan CRS, namun pada pendekatan VRS ketiga lembaga zakat tersebut efisien. Pada tahun 2019 LAZISNU mengalami inefisiensi pada pendekatan CRS, namun pada pendekatan VRS.Kata kunci: Efektivitas; Harmoni; Toleransi